Crystal structure of choline fenofibrate (Trilipix®), (C5H14NO) (C17H14ClO4). Issue 2 (4th April 2016) - Kaduk, James A.; Zhong, Kai; Gindhart, Amy M.; Blanton, Thomas N.
Abstract : The crystal structure of choline fenofibrate has been solved and refined using synchrotron X-ray powder diffraction data, and optimized using density functional techniques. Choline fenofibrate crystallizes in space group Pbca (#61) with a = 12.341 03(2), b = 28.568 70(6), c = 12.025 62(2) Å, V = 4239.84(1) Å 3, and Z = 8. The hydroxyl group of the choline anion makes a strong hydrogen bond to the ionized carboxylate group of the fenofibrate anion. Together with C–H···O hydrogen bonds, these link the cations and anions into layers parallel to the ac -plane. The powder pattern has been submitted to ICDD for inclusion in the Powder Diffraction File™.